The simplified form of the expression is [tex]\frac{1}{(t+4)^2}[/tex]
Given the expression:
Factorize the denominator as shown:
t^2 + 7t + 12
t^2 + 4t + 3t + 12
t(t+4) + 3(t+4)
(t+4)(t+3)
Substituting into the expression above, we will have:
[tex]= \dfrac{\frac{t+3}{t+4} }{(t+3)(t+4)}\\=\dfrac{t+3}{t+4} \div (t+3)(t+4)\\=\dfrac{t+3}{t+4} \times \dfrac{1}{(t+3)(t+4)} \\=\dfrac{1}{(t+4)^2}[/tex]
Hence the simplified form of the expression is [tex]\frac{1}{(t+4)^2}[/tex]
Learn more on indices here: https://brainly.com/question/15361818